Використання сучасних комп’ютерних технологій SolidWorks для обчислення коефіцієнту запасу сили гвинтового домкрату - Зябрев, А. В.; Захарова, Д. Р. (НТУ ДП, 2023)
У роботі розглядаються основні засади використання сучасних комп’ютерних технологій SolidWork для оцінки впливу величини підйому гвинтів домкрату на коефіцієнт запасу сили

In this article we survey the basic principles of using modern computer technologies SolidWork to assess the effect of the height of jack screws on the safety factor.
Using modern SolidWorks computer technologies for calculation the coefficient of the safety factor of the screw jack
Keywords: SolidWorks; гвинтовий домкрат; коефіцієнт запасу сили; дослідження; screw jack; safety factor; research